2022
DOI: 10.1111/zph.12949
|View full text |Cite
|
Sign up to set email alerts
|

First report and genotyping of Dientamoeba fragilis in pet budgerigars (Melopsittacus undulatus), with zoonotic importance

Abstract: The protozoan Dientamoeba fragilis is one of the most common parasites in the digestive system of humans worldwide. The host range and transmission routes of D. fragilis, including the role of animals, are still ambiguous with few reports from non‐human primates, sheep, rodents, pigs, a cat and a dog. In this study, we used microscopic and TaqMan qPCR analyses to investigate D. fragilisin 150 faecal samples from pet budgerigars (Melopsittacus undulatus) in the Central Anatolia Region of Turkey. Dientamoeba fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Similar to our study, the rate of parasites detected by the molecular method (21.33%) was significantly higher than the rate determined by the staining method (8.66%). In addition, it has F I G U R E 4 Evolutionary distances of identified Dientamoeba fragilis isolates and various trichomonads from different regions and hosts been reported that all of the isolates are genotype 1, as in all the limited number of studies on this subject, including ours (Yetismis et al, 2022).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Similar to our study, the rate of parasites detected by the molecular method (21.33%) was significantly higher than the rate determined by the staining method (8.66%). In addition, it has F I G U R E 4 Evolutionary distances of identified Dientamoeba fragilis isolates and various trichomonads from different regions and hosts been reported that all of the isolates are genotype 1, as in all the limited number of studies on this subject, including ours (Yetismis et al, 2022).…”
Section: Discussionmentioning
confidence: 59%
“…Although D. fragilis infection is generally asymptomatic in most of the cases, it is stated that non‐specific gastrointestinal findings such as loss of appetite, diarrhoea, constipation and nausea‐vomiting can be seen when symptomatic (Clemente et al, 2021; Girginkardeşler et al, 2003; Kurt et al, 2008; Sarzhanov et al, 2021; Sivcan et al, 2018; Stark et al, 2016; Yıldız et al, 2021). However, with the recent detection of the cyst form, it was thought that D. fragilis could also settle in non‐human hosts, and studies aiming to detect the parasite in animals gained momentum (Cacciò et al, 2012; Chan et al, 2016; Munasinghe et al, 2013; Ogunniyi et al, 2014; Yetismis et al, 2022). Unfortunately, although a few previous studies report the occurrence of D. fragilis in animals, there are almost no studies in the literature in which molecular methods were used for confirmation (Chan et al, 2016; Yetismis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations